The Place of Vocational Pedagogy in Pedagogical Science System - N. V. Ronzhina (Образование и наука, 2015)
The paper is devoted to defining the place of professional pedagogy in the system of pedagogic sciences. It is justified by the goal-setting idea that implies the competent personality development in the process of vocational training and life long self-development. The need for vocational pedagogy was caused by the social demand for the unified successive system of vocational training. The pedagogic problems can be divided according to the goal setting into the two main categories: integration into the social and natural environment (socialization), and integration in professional environment (professionalism). Therefore, pedagogy incorporates two main spheres: the general and vocational pedagogy, in which the other types of pedagogic knowledge are specified. In compliance with the goal setting, the pedagogic issues of teacher training are also divided into two groups: 1) training teachers for socialization system– the goal of pedagogic training; 2) training teachers for professional system – the goal of vocational teacher training. Such division is rather formal as every educational establishment within the framework of the federal educational standards provides up-bringing, general education, personal and civil growth, etc. However, the author demonstrates the specificity of general and vocational education in accordance with the set goals.